Organizing Intensive Mulberry Gardens in our Republic - Shavkat Ikromovich Achilov; Oybek Toshtemirovich Karimov; Davron Sodiq o’g’li Sodiqov (Zien Journals, 2023)
This article is aimed at strengthening the silkworm forage base in our republic, the organization of intensive mulberry plantations in clusters and farms, the scheme of their planting and the use of varietal mulberry groves.
Keywords: Intensive mulberry; mulberry tree; fodder mulberry; hybrid